Reproducibility and validity of diet quality scores derived from food-frequency questionnaires. Issue 3 (11th November 2021) - Yue, Yiyang; Yuan, Changzheng; Wang, Dong D; Wang, Molin; Song, Mingyang; Shan, Zhilei; Hu, Frank; Rosner, Bernard; Smith-Warner, Stephanie A; Willett, Walter C
ABSTRACT: Background: Diet quality scores (DQSs) are frequently used to study diet–disease relations but the validity of these scores derived from FFQs has rarely been evaluated. Objectives: To evaluate the validity and reproducibility of 6 commonly used DQSs derived from the FFQ, including the Alternate Healthy Eating Index–2010, Dietary Approaches to Stop Hypertension Trial score, alternative Mediterranean diet score, and 3 plant-based diet indices (overall, healthful, and unhealthful). Methods: This analysis included 1394 participants from the Men's Lifestyle Validation Study ( N = 652) and the Women's Lifestyle Validation Study ( N = 742). Participants completed a 152-item FFQ at the beginning of the study and 1 y later, as well as completed 2 weighed 7-d dietary records (7DDRs) and donated 2 blood samples 6 mo apart between FFQ assessments. The reproducibility of the FFQs was evaluated by rank intraclass correlation coefficients (ICCs). The validity was assessed by comparing FFQ-derived DQSs with those from the average of two 7DDRs using Spearman rank correlation coefficients deattenuated for random measurement error in the 7DDRs ( r s ). Furthermore, we calculated the correlations between DQSs and plasma biomarkers of diet, including fatty acids, folate, carotenoids, retinol, and α- and γ-tocopherol. Results: Six FFQ-derived DQSs demonstrated moderate to high reproducibility (energy-adjusted ICCs: 0.61–0.84) and validity (energy-adjusted, deattenuated r s = 0.56–0.80) in both men and women. We consistently observed expected correlations between FFQ-derived DQSs with plasma fatty acids, including long-chain n–3 (ω-3) and trans fatty acids, most carotenoids, and γ-tocopherol ( r s > 0.2). Conclusions: Our study demonstrates the validity of the FFQ to evaluate overall diet quality using 6 commonly used DQSs. In addition, these DQSs have qualitatively demonstrated biological relevance, as indicated by their correlations with circulating biomarkers.